2017
DOI: 10.4149/bll_2017_102
|View full text |Cite
|
Sign up to set email alerts
|

Bone metastases in neuroendocrine tumors

Abstract: Neuroendocrine tumors arise from various cells that form a part of the endocrine system and account for a small number of cases encountered by oncologists in clinical practice. The clinical incidence of these tumors used to be low, and newer imaging modalities have now begun to be used for detecting bone metastases at an earlier stage. Bone metastases arising from neuroendocrine tumors are a well-recognized complication. Their presence carries along a poor prognosis. Clinical symptoms are similar to those enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 4 publications
0
14
0
1
Order By: Relevance
“…Of note, it has been suggested that hypercalcemia is a rare finding in bone metastases secondary to NETs, with only 4% of cases being reported; hypercalcemia is more commonly associated with pheochromocytomas or sympathetic paragangliomas, compared to gastropancreatic carcinomas. 8 Another study revealed that 44–73% of patients with NETs present with metastatic disease, and bone involvement is likely underestimated and oftentimes found post-mortem. 9 …”
Section: Discussionmentioning
confidence: 99%
“…Of note, it has been suggested that hypercalcemia is a rare finding in bone metastases secondary to NETs, with only 4% of cases being reported; hypercalcemia is more commonly associated with pheochromocytomas or sympathetic paragangliomas, compared to gastropancreatic carcinomas. 8 Another study revealed that 44–73% of patients with NETs present with metastatic disease, and bone involvement is likely underestimated and oftentimes found post-mortem. 9 …”
Section: Discussionmentioning
confidence: 99%
“…NENs may affect the skeleton status through different mechanisms (23,24). On the one hand, there are well-established malignancy-related aspects which include: bone metastases potentially associated with pathological fractures (such as vertebral fractures or even atypical femoral fractures), vertebral/cord compression due to vertebral fractures, and paraneoplasic hypercalcemia (23,24).…”
Section: Skeleton-related Events In Nens With Metastatic Potentialmentioning
confidence: 99%
“…NENs may affect the skeleton status through different mechanisms (23,24). On the one hand, there are well-established malignancy-related aspects which include: bone metastases potentially associated with pathological fractures (such as vertebral fractures or even atypical femoral fractures), vertebral/cord compression due to vertebral fractures, and paraneoplasic hypercalcemia (23,24). The natural history of such incidental events largely varies due to the multiple subtypes of NENs; thus, a different behavior is expected, but the most important aspect in secondary dissemination is actually the tumor aggressive pattern rather than a particular histological type (25,26).…”
Section: Skeleton-related Events In Nens With Metastatic Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Kemik sintigrafisinde tespit edilen lezyonların direkt grafiyle incelenmesi ve kombine yaklaşımlarla, metastazların tespitinde ve tedavinin takibinde güvenilirlik artmıştır. [6] BT ve MR, direkt grafi ile de doğrulanan şüpheli kemik sintigrafi bulgularının değerlendirilmesinde çok etkindir. MR aynı zamanda, kemik metastazlarının kemikte sintigrafik olarak gösterilebilecek lezyonlarının metabolik değişiklik yapmadan önce görüntülenmesini sağladığından, çok değerli bir yöntem olarak kabul edilir.…”
Section: Radyoloji̇unclassified